Effect of occlusal reduction on post-operative pain of symptomatic and asymptomatic molar teeth - Aysenur Kamacı Esen; Fatma Furuncuoğlu; Fatima Betul Basturk; Muhammet Nuri Taşcıoğlu; Masoud Parirokh (Acta Odontologica Scandinavica)
Objective: This study aimed to compare the intensity of post-operative pain after single-visit root canal treatment of symptomatic or asymptomatic teeth following occlusal reduction.